A self-supporting high-strength silicon-carbon negative electrode and preparation method thereof
By using a porous self-supporting frame as a carrier in the silicon carbon anode of lithium-ion batteries, loaded silicon and carbon are deposited through chemical vapor phase and rolling, the problems of low structural strength and poor circulation stability of silicon carbon anode material are solved, and a high-strength, stable and low-cost silicon carbon anode material is achieved.
Patent Information
- Application Number
- CN202411050966.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The existing lithium-ion battery silicon carbon anode material has low structural strength, easy cracking, poor circulation stability, and poor practicality of the new process.
By preparing a dispersion of one-dimensional conductive material, freeze-drying to obtain a porous self-supporting frame, and then silicon and carbon are loaded on the frame by chemical vapor deposition and rolling to obtain a self-supported high-strength silicon-carbon negative electrode.
It has achieved a self-supported silicon carbon negative electrode with good mechanical properties, improved cycle stability, simple process, improved energy density and reduced cost.
Smart Images

Figure CN118748241B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a self-supporting high-strength silicon-carbon negative electrode and a preparation method thereof. Background Art
[0002] With the development of society, the rise of electric vehicles and large-scale energy storage, the energy density of existing lithium-ion batteries can no longer meet daily needs. Limited by the material system, the current commercial lithium-ion batteries are close to their energy density limit of 300Wh kg -1 , it is necessary to improve the energy density level by developing positive and negative electrode materials with higher specific capacity. Silicon has a high theoretical specific capacity (4200mAh g -1 ), low operating voltage and other characteristics have attracted extensive research, and it is abundant in the earth's crust, low in cost and environmentally friendly, making it one of the most promising next-generation lithium-ion battery negative electrode materials.
[0003] At present, the practicality of pure silicon is poor. Researchers have improved the practicality of silicon negative electrode materials by modifying them, such as nano-sizing of silicon particles, structural design of silicon materials, and preparation of composite materials such as silicon and carbon materials and polymers. At present, in the silicon-carbon composite system, silicon particles act as active substances to provide lithium storage capacity; carbon can not only buffer the volume change of the silicon negative electrode during charging and discharging, but also improve the conductivity of silicon materials and prevent silicon particles from agglomerating during the charge and discharge cycle. Despite this, the large stress generated by the phase change and volume expansion of silicon during the lithiation process will still cause the traditional coated electrode to break and pulverize, increase resistance, and drop sharply in cycle performance. Therefore, the research focus should not only focus on silicon-carbon negative electrode materials, but also start from the electrode structure, explore the electrode preparation process, optimize the electrode components and microstructure, improve the electrode strength, and improve the electrochemical performance of the silicon-carbon negative electrode.
[0004] Patent CN117878292A discloses a three-dimensional graphene-like self-supporting silicon-carbon composite material and its preparation method and application. A thin film porous carbon material is first prepared by melting and boiling an organic carbon source, and then silicon deposition and carbon coating processes are respectively carried out by chemical vapor deposition, and finally it is directly used as a negative electrode sheet for lithium-ion batteries. The structure of the porous carbon preparation process in this patent is uncontrollable, and the final silicon-carbon negative electrode performance consistency is poor; and the pole piece is plate-shaped, with poor flexibility, which is not conducive to later processing and has poor practicality. Patent CN117334858A discloses a double-coating layer structure self-supporting silicon-carbon negative electrode material and its preparation method. A carbon nanotube dispersion and a graphene oxide aqueous solution are mixed to obtain a carbon nanotube-graphene oxide solution, and then the carbon nanotube-graphene oxide solution, nanosilicon dispersion, and carbon nanotube-graphene oxide solution are vacuum filtered layer by layer in the order of vacuum filtration, and finally a polyaniline-coated self-supporting silicon-carbon composite electrode is obtained. The middle layer of the electrode is a pure silicon layer without a conductive agent. When the electrode load increases, it is difficult for electrons to conduct between silicon particles. In addition, the electrode preparation process is complicated and the electrode surface density is difficult to control, which is not conducive to large-scale continuous production.
[0005] Therefore, in view of the problems that the current traditional silicon-carbon negative electrode process has low structural strength, easy cracking, and poor cycle stability, while the new process has poor practicality, it is particularly important to develop a silicon-carbon negative electrode and its preparation method with good mechanical properties, stable structure, simple process. Summary of the invention
[0006] Based on this, the present invention provides a method for preparing a self-supporting high-strength silicon-carbon negative electrode with good mechanical properties, good cycle stability and simple process.
[0007] A method for preparing a self-supporting high-strength silicon-carbon negative electrode comprises the following steps:
[0008] A dispersion of a one-dimensional conductive material is prepared, and placed in a regular container for freeze drying to obtain a porous self-supporting frame; the cross-section of the accommodation space of the regular container is consistent with the shape and size of the target electrode, the concentration of the one-dimensional conductive material in the dispersion is 5wt% to 80wt%, and the height of the dispersion in the accommodation space of the regular container is 20 to 9000μm;
[0009] Loading silicon and carbon on the porous self-supporting framework by chemical vapor deposition to obtain a silicon-carbon negative electrode A;
[0010] The silicon-carbon negative electrode A is roll-pressed to obtain the self-supporting high-strength silicon-carbon negative electrode.
[0011] In one embodiment, the concentration of the one-dimensional conductive material in the dispersion is preferably 10 wt% to 25 wt%, and the height of the dispersion is preferably 100 μm to 200 μm.
[0012] In one embodiment, the material of the regular container is glass, organic polymer or metal. Optionally, the cross-section of the accommodation space of the regular container is consistent with the shape and size of the pole piece required for the assembly of the laminated battery, the wound battery, and the button battery. The pole piece includes a main body and a pole ear, which can avoid the subsequent pole piece cutting process. The pole piece can be directly used in the battery cell assembly process such as winding or lamination. It can be understood that the cross-section refers to the cross-section perpendicular to the direction of gravity when the regular container normally contains the dispersion.
[0013] In one embodiment, the one-dimensional conductive material is selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon fibers and metal nanowires, and the one-dimensional conductive material has a diameter of 1 nm to 5 μm, preferably 6 nm to 200 nm, a length of 20 nm to 1 mm, preferably 2 μm to 10 μm, and an aspect ratio of 5 to 10,000, preferably 50 to 330.
[0014] In one embodiment, the solvent of the dispersion is one or more of water, ethanol, acetone and N-methylpyrrolidone (NMP).
[0015] In one embodiment, the dispersion contains a dispersant with a concentration of 0.05wt% to 10wt%, and the dispersant is selected from one or more of polyvinyl pyrrolidone (PVP) and sodium carboxymethyl cellulose (CMC). In this way, the dispersion can be guaranteed to have good stability, and the internal components will not settle after standing for 72 hours. Preferably, the concentration of the dispersant is 0.5wt% to 1.5wt%.
[0016] In one embodiment, the mass ratio of the porous self-supporting frame in the silicon-carbon negative electrode A is 2% to 50%, preferably 5% to 10%, the mass ratio of silicon is 5% to 90%, preferably 30% to 60%, the mass ratio of carbon is 2% to 90%, preferably 35% to 62%, and the particle size of the deposited silicon particles is 5 to 500 nm, preferably 30 nm to 50 nm.
[0017] In one of the embodiments, in the process of loading silicon and carbon on the porous self-supporting frame by chemical vapor deposition, the silicon source gas and the carbon source gas are charged simultaneously, or the silicon source gas is charged first and then the carbon source gas, or the carbon source gas is charged first and then the silicon source gas, or the silicon source gas and the carbon source gas are charged alternately multiple times.
[0018] In one embodiment, the carbon source gas is selected from one or more of alkanes, alkynes, olefins and benzene ring gases, and the silicon source gas is selected from one or more of monosilane, disilane, trisilane and trichlorosilane.
[0019] In one embodiment, the carbon source gas or the silicon source gas accounts for 1 wt % to 10 wt % of the total gas.
[0020] In one embodiment, the pyrolysis temperature in the chemical vapor deposition is 300-1200° C., and the carrier gas used is selected from at least one of hydrogen, nitrogen, helium, neon, and argon.
[0021] In one embodiment, the porosity of the self-supporting high-strength silicon-carbon negative electrode is 5% to 70%, the tensile strength is 1 to 500 MPa, the deposited silicon and the deposited carbon are regarded as active materials, and the surface density of the electrode active material is 1 to 30 mg cm -2 .
[0022] The present invention also provides a self-supporting high-strength silicon-carbon negative electrode, which is prepared according to the above preparation method.
[0023] The present invention also provides a lithium-ion battery, which comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the above-mentioned self-supporting high-strength silicon-carbon negative electrode.
[0024] The above solution of the present invention has the following beneficial effects:
[0025] The porous framework in the present invention can play three roles in one: first, it acts as a binder. No additional binder is needed. The one-dimensional material has excellent tensile strength and will not break during the cycle, giving the pole piece excellent mechanical strength and ensuring cycle stability; second, it acts as a conductive agent. All deposited nano-silicon particles are attached to the one-dimensional conductive material. The pole piece has an excellent continuous three-dimensional conductive network inside, ensuring that the pole piece has a high reversible capacity; third, it acts as a current collector, which is the support framework of the silicon-carbon negative electrode. The three-in-one role of the porous framework can perfectly solve the problems of poor conductivity, easy pulverization, low mechanical strength and easy cracking of silicon particles at the same time, and the process advantages are outstanding; at the same time, the three-in-one role of the porous framework also greatly reduces the proportion of inert substances in the electrode, further improving the energy density of the silicon-carbon negative electrode of the present invention; and the present invention can directly obtain the silicon-carbon negative electrode from the raw material without the pulping process, greatly shortening the process and reducing the material, labor and time costs.
[0026] The present invention can produce a porous fiber framework with adjustable porosity, uniform structure and good batch consistency, which is used as a matrix for CVD preparation of silicon-carbon negative electrodes; compared with the porous framework of the present invention, the matrix of the current commercial CVD silicon-carbon negative electrode material is porous carbon, the raw material consistency is low, and the price is high, resulting in a high cost of the final silicon-carbon negative electrode material. The shape and size of the porous frame are the pole piece size required for the assembly of laminated batteries and wound batteries, avoiding the subsequent pole piece cutting process, and the electrode obtained after chemical vapor deposition can be directly used in the battery cell assembly process such as winding or lamination.
[0027] The abundant pores inside the porous frame of the present invention can ensure that the electrode has a faster ion liquid phase transmission speed. The pores also reserve space for the expansion of silicon particles, avoiding stress accumulation caused by the expansion of a large number of silicon particles, ensuring that the thickness of the electrode will not expand and shrink as a whole, effectively preventing the electrode from cracking, and giving the electrode excellent cycle stability; even if the silicon particles are pulverized in the later stage of the cycle, they are still confined in the frame, maintain electrical contact with the electrode, will not lose reactivity, and can continue to provide capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the structure of the silicon-carbon negative electrode prepared in Example 1 of the present invention;
[0029] Figure 2 Schematic diagram of the regular container used in Example 1 of the present invention, the left figure is a regular container corresponding to the laminated battery electrode sheet, and the right figure is a regular container corresponding to the wound battery electrode sheet;
[0030] Figure 3 This is a cycle performance diagram of the silicon-carbon negative electrode prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The reagents and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods without specific conditions in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books or methods recommended by the manufacturer.
[0033] The following are specific embodiments. Figure 1 The figure shows the structure of the silicon-carbon negative electrode prepared in the following Example 1, which has single-walled carbon nanotubes inside and silicon particles and a carbon coating layer deposited on the surface in sequence.
[0034] Example 1
[0035] A self-supporting high-strength silicon-carbon negative electrode and a preparation method thereof, comprising the following steps:
[0036] (1) preparing a dispersion of single-walled carbon nanotubes, wherein the carbon nanotubes have a diameter of 6 nm, a length of 2 μm, an aspect ratio of 330, a concentration of 10 wt %, a solvent of water, a dispersant of CMC, a concentration of 0.5 wt %, and are placed in a regular container with a dispersion height of 100 μm, and a porous self-supporting framework is obtained by freeze drying; Figure 2 Shown is a schematic diagram of the cross-sectional shape of the regular container used, in which the pole piece formed after the dispersion is freeze-dried has a main body and pole ears. The left figure is a regular container corresponding to the laminated battery pole piece, and the right figure is a regular container corresponding to the wound battery pole piece.
[0037] (2) The porous self-supporting framework obtained in (1) is used as a carrier, and silicon and carbon are deposited on the framework by chemical vapor deposition; silicon deposition is first performed, the silicon source is monosilane, the carrier gas is nitrogen, and the pyrolysis temperature is 600°C; then carbon deposition is performed, the carbon source is methane, the carrier gas is argon, and the pyrolysis temperature is 700°C. The chemical vapor deposition conditions are controlled, and the particle size of the silicon particles is 40nm; the porous framework mass in the silicon-carbon negative electrode A accounts for 5wt%, the deposited silicon accounts for 60wt%, and the deposited carbon accounts for 35wt%.
[0038] (3) The silicon-carbon negative electrode A obtained in (2) was roll-pressed to obtain a silicon-carbon negative electrode B having a porosity of 40%, a tensile strength of 30 MPa, and an electrode active material surface density of 5 mg cm -2 .
[0039] The electrodes are cut into discs (if used for laminated batteries or wound batteries, no cutting is required), which is convenient for button battery assembly and testing of electrochemical performance. The electrolyte solute is LiPF6, and the solvent is EC, DMC, and DEC. The volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . The charge and discharge test was carried out between 0.01 and 1.5 V (at a current density of 50 mA g -1 The first three charge and discharge tests were carried out at a current density of 200 mA g -1 The electrochemical performance is shown in Table 1.
[0040] Example 2
[0041] A self-supporting high-strength silicon-carbon negative electrode and a preparation method thereof, comprising the following steps:
[0042] (1) preparing a dispersion of copper nanowires, wherein the copper nanowires have a diameter of 100 nm, a length of 5 μm, an aspect ratio of 50, a concentration of 20 wt %, a solvent of NMP, a dispersant of PVP, a concentration of 1 wt %, and are placed in a regular container with a dispersion height of 200 μm, and a porous self-supporting framework is obtained by freeze drying;
[0043] (2) The porous self-supporting framework obtained in (1) is used as a carrier, and silicon and carbon are deposited on the framework by chemical vapor deposition; silicon and carbon are deposited together, the silicon source is monosilane, the carbon source is methane, the carrier gas is nitrogen, and the pyrolysis temperature is 800°C; the chemical vapor deposition conditions are controlled, and the particle size of the silicon particles is 30nm; the mass of the porous framework in the silicon-carbon negative electrode A accounts for 8wt%, the deposited silicon accounts for 30wt%, and the deposited carbon accounts for 62wt%.
[0044] (3) The silicon-carbon negative electrode A obtained in (2) was roll-pressed to obtain a silicon-carbon negative electrode B having a porosity of 35%, a tensile strength of 25 MPa, and an electrode active material surface density of 8 mg cm -2 .
[0045] The electrodes are cut into discs for convenient assembly of button cells and testing of electrochemical performance. The electrolyte solute is LiPF6, and the solvents are EC, DMC, and DEC. The volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . Perform charge and discharge tests between 0.01 and 1.5 V (at a current density of 50 mAg -1 The first three charge and discharge tests were carried out at a current density of 200 mAg -1 The electrochemical performance is shown in Table 1.
[0046] Example 3
[0047] (1) preparing a dispersion of carbon fibers, wherein the carbon fibers have a diameter of 200 nm, a length of 10 μm, an aspect ratio of 50, a concentration of 25 wt %, an ethanol solvent, and a PVP dispersant at a concentration of 1.5 wt %, placed in a regular container, and a dispersion height of 150 μm, and freeze-dried to obtain a porous self-supporting framework;
[0048] (2) The porous self-supporting framework obtained in (1) is used as a carrier, and silicon and carbon are deposited on the framework by chemical vapor deposition; silicon deposition is first performed, the silicon source is monosilane, the carrier gas is nitrogen, and the pyrolysis temperature is 700°C; then carbon deposition is performed, the carbon source is ethylene, the carrier gas is argon, and the pyrolysis temperature is 900°C. The chemical vapor deposition conditions are controlled, and the particle size of the silicon particles is 50nm; the porous framework mass in the silicon-carbon negative electrode A accounts for 10wt%, the deposited silicon accounts for 50wt%, and the deposited carbon accounts for 40wt%.
[0049] (3) The silicon-carbon negative electrode A obtained in (2) was roll-pressed to obtain a silicon-carbon negative electrode B having a porosity of 45%, a tensile strength of 35 MPa, and an electrode active material surface density of 6 mg cm -2 .
[0050] The electrodes are cut into discs for convenient assembly of button cells and testing of electrochemical performance. The electrolyte solute is LiPF6, and the solvents are EC, DMC, and DEC. The volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . Perform charge and discharge tests between 0.01 and 1.5 V (at a current density of 50 mAg -1 The first three charge and discharge tests were carried out at a current density of 200 mAg -1 The electrochemical performance is shown in Table 1.
[0051] In order to highlight the beneficial effects of the present invention, the following comparative examples are now provided for the embodiments:
[0052] Comparative Example 1
[0053] The active material is a commercial silicon-carbon anode prepared by chemical vapor deposition, with a silicon content of 60wt%, a silicon particle size of 40nm, a conductive agent Super P, and a binder PVDF, with a mass ratio of 0.9:0.05:0.05. The solid content of the slurry is controlled to be 60%, stirred for 6h, and the slurry is coated on a copper foil. The electrode is dried and then rolled. The surface density of the obtained electrode is 5mg cm -2 , the electrode porosity is 40%. Half-cell tests were conducted under the same test conditions, and the results are shown in Table 1.
[0054] Table 1 Comparison of the performance of silicon carbon electrodes between comparative example 1 and embodiment 1
[0055]
[0056] It can be seen from Table 1 that the capacity retention rate of the self-supporting high-strength silicon-carbon electrode of the present invention is higher. Thanks to the more excellent electrode structure, the electrode cracking caused by silicon expansion and contraction is effectively avoided, thereby ensuring the cycle stability of the electrode.
[0057] Comparative Example 2
[0058] The active material is a commercial silicon-carbon anode prepared by chemical vapor deposition, with a silicon content of 30wt%, a silicon particle size of 30nm, a conductive agent Super P, and a binder PVDF, with a mass ratio of 0.9:0.05:0.05. The solid content of the slurry is controlled to be 60%, stirred for 6h, and the slurry is coated on a copper foil. The electrode is dried and rolled, and the surface density of the obtained electrode is 8mg cm -2 , the electrode porosity is 35%. Half-cell tests were conducted under the same test conditions, and the results are shown in Table 2.
[0059] Table 2 Performance comparison of silicon carbon electrodes between comparative example 2 and example 2
[0060]
[0061]
[0062] It can be seen from Table 2 that the capacity retention rate of the self-supporting high-strength silicon-carbon electrode of the present invention is higher, the copper nanowires give the electrode excellent mechanical strength, and the abundant pores between the internal fibers reserve space for silicon expansion. The electrode structure is stable during the cycle, so the electrode electrochemical performance is more excellent.
[0063] Comparative Example 3
[0064] The active material is a commercial silicon-carbon negative electrode prepared by chemical vapor deposition, with a silicon content of 50wt%, a silicon particle size of 50nm, a conductive agent Super P, and a binder PVDF, with a mass ratio of 0.9:0.05:0.05. The solid content of the slurry is controlled to be 60%, stirred for 6h, and the slurry is coated on a copper foil. The electrode is dried and rolled, and the surface density of the obtained electrode is 6mg cm -2 , the electrode porosity is 45%. Half-cell tests were conducted under the same test conditions, and the results are shown in Table 3.
[0065] Table 3 Performance comparison of silicon carbon electrode between comparative example 3 and embodiment 3
[0066]
[0067] It can be seen from Table 3 that the capacity retention rate of the self-supporting high-strength silicon-carbon electrode of the present invention is higher, the carbon fiber gives the electrode excellent mechanical strength, and the abundant pores between the internal fibers reserve space for silicon expansion. The electrode structure is stable during the cycle, so the electrode electrochemical performance is more excellent.
[0068] Comparative Example 4
[0069] This comparative example is basically the same as Example 1, except that the dispersion of single-walled carbon nanotubes is spray-dried to obtain carbon nanotube microspheres, and then the carbon nanotube microspheres are used as a matrix to load silicon and carbon through chemical vapor deposition to obtain a carbon-silicon negative electrode material with a silicon content of 60wt% and a silicon particle size of 40nm. The carbon-silicon negative electrode material is then made into a pole piece according to the following steps: active material, conductive agent Super P, binder PVDF, mass ratio of 0.9:0.05:0.05, control the solid content of the slurry to 60%, stir for 6h, coat the slurry on copper foil, and roll the pole piece after drying. The surface density of the obtained pole piece is 5mg cm -2 , the electrode porosity is 40%. Half-cell tests were conducted under the same test conditions, and the results are shown in Table 4.
[0070] Table 4 Comparison of the performance of silicon carbon electrodes between comparative example 4 and embodiment 1
[0071]
[0072]
[0073] It can be seen from Table 4 that the capacity retention rate of the self-supporting high-strength silicon-carbon electrode of the present invention is higher and the electrochemical performance is more excellent. Compared with the traditional coated electrode, the electron transport network of the self-supporting electrode of the present invention is more excellent due to the presence of carbon nanotubes, the electrochemical reversibility is better, the mechanical strength is also higher, and the electrode structure is stable during the cycle, so the electrode electrochemical performance is more excellent.
[0074] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a self-supporting high-strength silicon-carbon negative electrode, characterized in that: The following steps are involved: A dispersion of a one-dimensional conductive material is prepared, and the dispersion is placed in a regular container for freeze drying to obtain a porous self-supporting frame; the cross-section of the accommodation space of the regular container is consistent with the shape and size of the target electrode, the concentration of the one-dimensional conductive material in the dispersion is 5wt% to 80wt%, and the height of the dispersion in the accommodation space of the regular container is 20 to 9000μm; wherein the one-dimensional conductive material is selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon fibers and metal nanowires, the diameter of the one-dimensional conductive material is 1nm to 5μm, the length is 20nm to 1mm, and the aspect ratio is 5 to 10000; Silicon and carbon are loaded onto the porous self-supporting frame by chemical vapor deposition to obtain a silicon-carbon negative electrode A; wherein, in the process of loading silicon and carbon onto the porous self-supporting frame by chemical vapor deposition, silicon source gas and carbon source gas are charged simultaneously, or silicon source gas is charged first and then carbon source gas, or carbon source gas is charged first and then silicon source gas, or silicon source gas and carbon source gas are charged alternately multiple times; The silicon-carbon negative electrode A is roll-pressed to obtain the self-supporting high-strength silicon-carbon negative electrode.
2. The preparation method according to claim 1, characterized in that: The material of the regular container is glass, organic polymer or metal.
3. The preparation method according to claim 1, characterized in that: The solvent of the dispersion is one or more of water, ethanol, acetone and N-methylpyrrolidone.
4. The preparation method according to claim 1, characterized in that: The dispersion contains a dispersant with a concentration of 0.05wt% to 10wt%, and the dispersant is selected from one or more of polyvinyl pyrrolidone and sodium carboxymethyl cellulose.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the porous self-supporting framework in the silicon-carbon negative electrode A is 2% to 50%, the mass ratio of silicon is 5% to 90%, the mass ratio of carbon is 2% to 90%, and the particle size of the deposited silicon particles is 5 to 500 nm.
6. The preparation method according to claim 1, characterized in that: The carbon source gas is selected from one or more of alkane, alkyne, olefin and benzene ring gases, and the silicon source gas is selected from one or more of monosilane, disilane, trisilane and trichlorosilane.
7. A self-supporting high-strength silicon-carbon negative electrode, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
8. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the self-supporting high-strength silicon-carbon negative electrode as claimed in claim 7.
Citation Information
Patent Citations
Self-supporting silicon-carbon negative electrode material with double-coating-layer structure and preparation method of self-supporting silicon-carbon negative electrode material
CN117334858A
Three-dimensional graphene-like self-supporting silicon-carbon composite material as well as preparation method and application thereof
CN117878292A
Method for preparing lithium ion battery silicon-carbon anode material by using carbon nanotube
CN109830668A
Silicon-based negative electrode material and preparation method thereof
CN116914112A